2020
DOI: 10.1111/ctr.14060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of temporary mechanical circulatory support for early graft failure on post–heart transplantation outcomes

Abstract: Although temporary mechanical circulatory support (tMCS) for hemodynamic failure following heart transplantation is associated with increased early morbidity and mortality, the impact of etiology of graft dysfunction and long-term clinical implications are less well known. The objective of our study was to evaluate outcomes in patients who required venoarterial extracorporeal membrane oxygenation (VA ECMO) or temporary right ventricular assist device (RVAD) support for either primary or secondary early graft d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…10 Our rate of positive donor cultures is similar to previously reported literature, 68.7% vs 28.7%-89%, respectively. 1,3,4,[11][12][13][14] Staphylococcus aureus was isolated from 87 (59%) donor respiratory cultures which also aligns with recently published data that evaluated perioperative antibiotic selection in lung transplant recipients, demonstrating a predominance of Staphylococcus aureus in donor respiratory cultures. 1 In contrast, recipient respiratory cultures post-transplant were predominated by Gram-negative organisms with a higher incidence of Enterobacteriales and Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 83%
“…10 Our rate of positive donor cultures is similar to previously reported literature, 68.7% vs 28.7%-89%, respectively. 1,3,4,[11][12][13][14] Staphylococcus aureus was isolated from 87 (59%) donor respiratory cultures which also aligns with recently published data that evaluated perioperative antibiotic selection in lung transplant recipients, demonstrating a predominance of Staphylococcus aureus in donor respiratory cultures. 1 In contrast, recipient respiratory cultures post-transplant were predominated by Gram-negative organisms with a higher incidence of Enterobacteriales and Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 83%
“…Urban, et al has shown that survival to discharge in PGD-LV patients was 40% and those with PGD-RV was 33% with their data indicating a high rate of cardiac recovery, specifically 100% for PGD-RV and 60% for PGD-LV. As to the deployment of the device, the group has shown that even delayed RVAD implantation in patients with posttransplantation RV failure due to increased afterload did not negatively impact the outcome as long as the support was implemented prior to any form of multiorgan failure [16 ▪ ].…”
Section: Post-transplantmentioning
confidence: 99%
“…Patients with worsening RV failure in the presence of severe LV diastolic dysfunction (demonstrated by elevated pulmonary artery wedge pressure) are at increased risk of developing LV systolic dysfunction after isolated RVAD insertion and thus may require biventricular support with VA-ECMO. There is some evidence that there is no difference in short-term survival independent of type of cannulation, whether central or peripheral [16 ▪ ].…”
Section: Post-transplantmentioning
confidence: 99%
“…PGF can present as left ventricular or bi‐ventricular dysfunction not attributable to a known cause 4 with risk factors including younger age at transplant, underlying diagnosis of CHD and HTx while on ECMO support 5 . Secondary graft failure can be seen in the context of vasoplegia, hyperacute rejection, surgical complications, or isolated RV dysfunction secondary to elevated PVR 6,7 . However, VAD therapy does present a number of challenges in the pediatric transplant patient population due to the increased risk of infection and impaired wound healing in the context of immunosuppression and the inability to support the failing graft, especially in those patients with allograft vasculopathy.…”
Section: Introductionmentioning
confidence: 99%